Monitoring the Realisation of the Right to Basic Education: The South African Jurisprudence and Structural-Process-Outcome Indicators - Kamga, Serges (Comparative and International Law Journal of Southern Africa, 2021)
Under international law, the right to education should be available, accessible, acceptable, and adaptable—or comply with the four As. This right is provided for by the South African Constitution and numerous policies. Yet it remains illusory for thousands of South Africans. Against this backdrop, this article seeks to clarify indicators to monitor the implementation of this right. To this end, unpacking the South African jurisprudence on the right to basic education, it relies on the structural-process-outcome indicators model to unveil what needs to be done to secure a tangible enjoyment of the right to basic education. Based on this approach, it finds that the right to basic education is multidimensional and that its constitutive elements include immediate and non-discriminatory access to school buildings; infrastructure; the right to teachers and non-educational staff; the right to enjoy religion, language, and culture; as well as free transport for learners living far from the school. Ultimately, in light of the South African jurisprudence, the structural-process-outcome indicators explain what is effectively expected to operationalise the four As. Lessons gleaned from this approach will enable all stakeholders in South Africa and other parts of Africa to advance the right to basic education.